"Superabundant Being": Disambiguating Rilke and Heidegger - Pfau, Thomas (Modern theology, 2019)
Rilke's impact on the generation of writers reshaping philosophy and theology during the interwar years is arguably without parallel. Within this constellation, the case of Heidegger as a reader of Rilke presents unique challenges. For Rilke's poetry neither quite allows for a wholly appropriative reading such as, for better or worse, Heidegger accords Hölderlin's oeuvre; nor can Heidegger quite bring himself to subject Rilke's poetry to critical appraisal. Instead, Heidegger's analysis of Dasein as worked out in Part I of Being and Time (1927) and in his lectures on The Basic Concepts of Metaphysics (1929) seems haunted by an intellectual and expressive debt to Rilke that he can neither acknowledge nor fully resolve. For to do so would be to confront a possibility of human finitude, so luminously traced in Rilke's Duino Elegies (1922), still defined by moments of transcendence - moments that can be captured in the fleeting plenitude of poetic intuition (Anschauung) and lyric image (Bild). Whereas von Balthasar, in volume 3 of his Apokalypse der deutschen Seele (1939), reads Rilke as fundamentally embracing Heidegger's notion of strictly immanent and finite Dasein, I argue that the oeuvre of the later Rilke, without being reclaimed for a metaphysical, let alone religious position, nevertheless is shaped, both intellectually and expressively, by insistent, if enigmatic, moments of transcendence.